Exploring the promise of intersectionality for promoting justice-involved women's health research and policy - Keren Gueta (BMC, 2020)
Abstract The perspective of intersectionality has gained widespread scholarly interest and been employed across many different disciplines, including criminology. This perspective focuses on interlocking systems of oppression and the need to work toward structural changes to promote social justice and equity. The present article aimed to explore the potential of intersectionality for advancing health research and policy regarding justice-involved women, in different phases of the judicial process, based on the extant literature. First, employing an intersectional approach to analyze the issue of health during the pre-incarceration period may facilitate identification of the structural and representational factors underlying the barriers that women face in obtaining health services, which elevates the risk to their health. Furthermore, adopting an intersectionality perspective to explore women's health during incarceration may shed light on vulnerable, invisible subpopulations of women such as incarcerated older women and their health problems, and help identify the structural barriers to carceral health services and the role of stigma in inflicting and normalizing harmful practices within prison walls. In addition, an intersectionality lens highlights the risk of unintended use of scholarly knowledge regarding the health of justice-involved women. Last, an intersectionality perspective is particularly relevant for research of the reentry of justice-involved women. In particular, it can be used to examine gender-sensitive reentry services that ignore other axes of marginalization, such as class and race, generating a powerful dynamic that results in partial service, denial of access to therapeutic resources, and possible exposure to health-damaging environments. Through an exploration of the extant literature on justice-involved women, I endeavored to demonstrate that an intersectional framework offers powerful tools to both challenge and strengthen gender frameworks within criminology. This will make it possible to move beyond consideration of gender alone, to understand how systems of oppression based on race, age and other social locations intersect and combine to construct health disadvantages among justice-involved women. This highlights the needs for a new research agenda and policy that integrate the intersectional framework with health theories to provide a more developed understanding of health among justice-involved women.